Simultaneous quantitation of hexacosanoyl lysophosphatidylcholine, amino acids, acylcarnitines, and succinylacetone during FIA–ESI–MS/MS analysis of dried blood spot extracts for newborn screening - Haynes, Christopher A. (Clin Biochem, 2015)
OBJECTIVES: The goal of this study was to include the quantitation of hexacosanoyl lysophosphatidylcholine, a biomarker for X-linked adrenoleukodystrophy and other peroxisomal disorders, in the routine extraction and analysis procedure used to quantitate amino acids, acylcarnitines, and succinylacetone during newborn screening. Criteria for the method included use of a single punch from a dried blood spot, one simple extraction of the punch, no high-performance liquid chromatography, and utilizing tandem mass spectrometry to quantitate the analytes. DESIGN AND METHODS: Dried blood spot punches were extracted with a methanolic solution of stable-isotope labeled internal standards, formic acid, and hydrazine, followed by flow injection analysis–electrospray ionization–tandem mass spectrometry. RESULTS: Quantitation of amino acids, acylcarnitines, and hexacosanoyl lysophosphatidylcholine using this combined method was similar to results obtained using two separate methods. CONCLUSIONS: A single dried blood spot punch extracted by a rapid (45 min), simple procedure can be analyzed with high throughput (2 min per sample) to quantitate amino acids, acylcarnitines, succinylacetone, and hexacosanoyl lysophosphatidylcholine.